Problematika Kinerja Guru Pendidikan Agama Islam dalam Meningkatkan Mutu Pendidikan - Ruslan, Ruslan; Syafi’ie, Moh. (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
The performance of Islamic Religious Education (IRE) teachers is instrumental in shaping students' character, morals, and religious knowledge, thus greatly affecting the overall quality of education. However, in practice, various challenges and obstacles are often faced, such as limited resources, less innovative teaching methods, and limited support from the school and government. This study aims to identify teacher performance problems and their implications in efforts to improve the quality of education at MTs. Raudlatul Ulum Lenteng sub-district, Sumenep district. This study uses a qualitative approach with the type of field research. The research subjects consisted of several IRE teachers, the curriculum section, and the head of madrasah. Data were obtained using interviews, observation, and documentation. The results showed that the performance of IRE teachers at MTs. Raudlatul Ulum Kec. Lenteng, Kab. The performance of PAI teachers in efforts to improve the quality of education at MTs Raudlatul Ulum still needs to be improved. This can be seen from the commitment of educators, especially IRE teachers who are still relatively low in carrying out their duties and obligations as a professional teacher. This condition then has implications for the quality of education which is also not by the established quality standards